Lessons from the application of knock-for-knock clauses under Malaysian law - Wan Zahari, Wan Mohd. Zulhafiz (Informa Law from Routledge, 2023)
This chapter discusses the application of knock-for-knock in countries unaccustomed with the clause. The use of legal provisions without a proper understanding of them will cause the indemnity and hold harmless clauses to be interpreted outside their meaning, potentially opening the door to abuse by a party in a dominant position.